The anthropocene and popular culture - Barron, Lee (Emerald points., 2025)
The Anthropocene and Popular Culture examines the proposition that geology and humanity have connected to constitute a new epoch: the Anthropocene. Critically exploring the nature, present and potentially future catastrophic global environmental transformations of this epoch, the chapters through the analysis of Anthropocene-themed popular cultural representations. Adding to what is still a relatively small core of texts that link the Anthropocene to popular culture, author Lee Barron provides a new set of case studies in one text that brings together representations of the Anthropocene from the perspectives of literature, film, television, celebrity and environmental discourses, and popular music. Aligning sociological and popular science approaches to the Anthropocene with perspectives drawn from speculative design, the chapters are accessible to readers from a range of disciplinary backgrounds, examining key approaches to the concept and its impact, and discussing political, cultural philosophical and sociological analysis of the Anthropocene from the perspectives of theorists such as Bruno Latour, Dipesh Chakrabarty, Ian Angus, Andreas Malm, Carolyn Merchant, Roy Scranton, Nigel Clark, Jamie Lorimer, Donna Haraway, Diane Ackerman, Mark Bould, and Sverre Raffnsøe. With promising appeal for scholars of applied and cultural sociology and disciplines regarding sustainability studies and human environmental impacts, The Anthropocene and Popular Culture is also interesting reading for the subdisciplines of media and cultural studies, and environmental studies of literature.